Seaweed biodiversity and temperature fluctuations of Calatagan Bay, Verde Island passage - Abeledo, Chona Camille V. (Animo Repository, 2019)
Changes in seaweed biodiversity reflect ecological changes and management of coastal communities. Calatagan Bay is a tourism, agriculture and aquaculture hotspot fronting the Verde Island Passage, touted to be the global center of marine biodiversity. Detection of stressors through monitoring is the key in the proper management of the area. This study surveyed existing seaweed species of the coast, and contrasted it with reported species in the area together with fluctuations in sea surface temperatures for the past two decades, contrasted with the local knowledge and perspectives of local coast-dwellers. Seaweed along the coast were collected from a representative area of 50 km2 with species identification based on morphology and pigment. Ten species that were previously unreported were found while fourteen previously reported species were no longer observed. Caulerpa, Kappaphycus and Sargassum, all with known market demands, were the dominant genera. Sea surface temperature data from local weather stations and the NOMADs database indicate significant warming events from June 1998 to present, with peak sea surface temperature at 31.9oC. Focused group discussions with local communities indicate increased incidences of ice-ice disease, and issues with the uncontrolled use of fertilizers of neighboring farms contaminating their coastal fronts.